2020
DOI: 10.3390/life10040043
|View full text |Cite
|
Sign up to set email alerts
|

Update Review about Metabolic Myopathies

Abstract: The aim of this review is to summarize and discuss recent findings and new insights in the etiology and phenotype of metabolic myopathies. The review relies on a systematic literature review of recent publications. Metabolic myopathies are a heterogeneous group of disorders characterized by mostly inherited defects of enzymatic pathways involved in muscle cell metabolism. Metabolic myopathies present with either permanent (fixed) or episodic abnormalities, such as weakness, wasting, exercise-intolerance, myalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 90 publications
2
12
0
3
Order By: Relevance
“…In other words, muscles of Tfam KO mice showed an increased muscle fatigue before entering the state with progressive muscle atrophy and muscle weakness. These results extend those from previous studies showing a severe muscle weakness in more advanced stages of the disease (Gineste et al, 2015;Wredenberg et al, 2002) and support those reported in patients related to a progression from early premature fatigue to disabling muscle weakness already at rest (Finsterer, 2020;Tarnopolsky, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In other words, muscles of Tfam KO mice showed an increased muscle fatigue before entering the state with progressive muscle atrophy and muscle weakness. These results extend those from previous studies showing a severe muscle weakness in more advanced stages of the disease (Gineste et al, 2015;Wredenberg et al, 2002) and support those reported in patients related to a progression from early premature fatigue to disabling muscle weakness already at rest (Finsterer, 2020;Tarnopolsky, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Premature muscle fatigue (i.e., faster decline in force during sustained or repeated contractions) is a typical feature in patients with mitochondrial myopathy (Finsterer, 2020;Tarnopolsky, 2016). We measured force production during 80 repeated submaximal contractions (1.5 s contractions given every 7.5 s).…”
Section: Faster Fatigue In Tfam Ko Than In Wt Mice At 11 and 14 Weeksmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted October 18, 2022. ; https://doi.org/10.1101/2022.10.14.511701 doi: bioRxiv preprint mitochondrial myopathies (16)(17)(18). Intriguingly, the CsA treatment-induced protection against muscle weakness, weight loss and early death in Tfam KO mice was not accompanied by any obvious signs of improved mitochondrial respiration, as judged from unaffected expression of proteins involved in mitochondrial energy metabolism (15).…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding strenuous exercise in fasted-states or during ongoing infections, along with dietary modifications (high carbohydrate and low fat) are the mainstays for management strategies [ 6 ]. Overall, current recommendations for metabolic myopathies advocate for supportive therapy and symptomatic management, ranging from routine cardiac monitoring to invasive ventilation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%